소나무 수관 층위별 솔잎혹파리 충영 형성률의 예측 모델 - 이창현; Changhyun Lee; 박준형; Junhyung Park; 안효준; Hyojun Ahn; 서다혜; Dahye Seo; 박중열; Joong Yeol Park; 홍성원; Sungwon Hong; et al. (한국산림과학회지, 2025)
본 연구에서는 소나무(Pinus densiflora)를 대상으로 솔잎혹파리(Thecodiplosis japonensis)의 충영 형성률을 수관 층위별로 비교하였다. 2024년 10월, 경북 영덕군의 솔잎혹파리 피해 임지에서 수고가 유사한 소나무 20본을 무작위로 선정하여 하층(3~4 m), 중층(5~6 m), 상층(7~8 m)에서 총 60,028개의 침엽을 채취하였다. 충영은 주로 잎 기부에 위치하였고 일부 중간 부위에서도 확인되었다. 충영이 형성된 잎은 건전 잎보다 평균 5 cm 짧았으며, 충영 내부에서 평균 2마리의 유충이 관찰되었다. 히트맵분석을 통한 충영의 분포는 수관 상층에 집중되는 경향을 보였다. 수관 층위별 충영 형성률은 이항 분포(Binomial distribution)에 기반한 일반화 선형 혼합 모델(Generalized linear mixed model; GLMM)로 분석하였다. 관측된 형성률은 상층 51.0%, 중층 31.1%, 하층 23.0%로 나타났으며, 층위가 높아질수록 유의하게 증가하였다(p < 0.05). 예측된 충영 형성률은 관측값과 유의미하게 일치하였다. 하층(R 2 =0.37)과 중층(R 2 =0.57)을 활용한 모델보다 하층과 중층의 결합 모델(R 2 =0.67)의 예측력이 높았다. 이러한 결과는 솔잎혹파리 피해 예찰 및 방제전략 수립 시 수관 내 조사 부위 기준 설정의 기초자료로 활용할 수 있다. This study investigated gall formation in Pinus densiflora caused by Thecodiplosis japonensis, focusing on differences among canopy layers. In October 2024, twenty P. densiflora trees of similar heights were randomly selected from a forest stand infested by T. japonensis in Yeongdeok-gun, Gyeongsangbuk-do, South Korea. In total, 60,028 needles were sampled from the lower (3-4 m), middle (5-6 m), and upper (7-8 m) canopy layers. Galls were primarily located near the needle base, although some were also found in the middle portion, and each gall typically contained approximately two larvae. Needles with galls were on average 5 cm shorter than healthy needles. Heatmap analysis revealed a clear concentration of galls in the upper canopy. Gall formation across canopy layers was analyzed using a generalized linear mixed model with a binomial distribution. According to the results, 51.0%, 31.1%, and 23.0% of gall formation occurred in the upper, middle, and lower layers, respectively, revealing significant differences among the layers (p < 0.05). The predicted pattern of gall formation was consistent with these observations. The prediction model using gall formation in the lower and middle layers exhibited greater predictive accuracy (R 2 = 0.67) than models using the lower (R 2 = 0.37) or middle layer alone (R 2 = 0.57). These results provide fundamental data for establishing survey standards within canopies for T. japonensis monitoring and management.